![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: y=sinx+cosx graph - y=sinx+cosx - y=sinx+cosx/sinx-cosx - y=x^tanx+sinx^cosx - y=e^x(sinx+cosx) - y=sinx^cosx find dy/dx - y sinx cosx - y=sinx cosx derivative - (1+cosx)y'=sinx(sinx+sinx cosx-y) - cos(x+y)=cosx cosy-sinx siny - (cosx+cosy)^2+(sinx-siny)^2=4cos^2x+y)/2 - cos(x+y)=cosx cosy-sinx siny proof - sinx-siny/cosx+cosy=tan x-y/2 - (cosx-cosy)^2+(sinx-siny)^2=4sin^2x-y/2) - y=sinx+cosx Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.